TYPES OF GRAMMATICAL CATEGORIES IN ENGLISH AND UZBEK - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Abstract: if we take Verb to discuss we can say that: according to content, verbs can be Described as words denoting actions, the term “actions” embracing the meaning of activity (e.g. to walk, to speak, to play, to study), process (e.g. to sleep, to wait, to live), state (e.g. to Be, to like, to know), relation (e.g. to consist, to resemble, to lack) and so on. According to Form, verbs can be described as words that have certain grammatical features that are not Shared by other parts of speech, e.g. they have the categories of tense, aspect, voice, etc. According to function, verbs can be defined as words making up the predicate of the